Pelatihan Strategi Digital Marketing untuk UMKM Aisiyah Kabupaten Banyumas - Erna Handayani; Irawan Randikaparsa (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
Small and Medium Enterprises are priority economic motors that are of concern to the government. The problem is that this sector still has many weaknesses, both in terms of capital, innovation, production and marketing. taking the marketing side, very important MSMEs are transforming from traditional marketing systems to digital marketing. For this reason, it is necessary to increase the capability of MSME business actors in the field of digital marketing. This community service activity aims to introduce and develop the ability of MSME business actors, especially MSME Aisiyah, Banyumas Regency in marketing digital products. The training is not only introduction, but also practice in the use of digital marketing media, including market achievement strategies in product development.